Bioprospection and Selection of Peptides by Phage Display as Novel Epitope-Based Diagnostic Probes for Serological Detection of HTLV-1 and Use in Future Vaccines - Luiz Fernando Almeida Machado; Luiz Fernando Almeida Machado; Luiz Ricardo Goulart Filho; Fabiana Almeida Araújo Santos; Leonardo Quintão Siravenha; Andrea Nazaré Monteiro Rangel Silva; Maria Alice Freitas Queiroz; Antonio Carlos Rosário Vallinoto; Antonio Carlos Rosário Vallinoto; Marluísa Oliveira Guimarães Ishak; Ricardo Ishak; Ricardo Ishak (Frontiers in Medicine, 2022)
Human T-lymphotropic virus 1 (HTLV-1) is endemic worldwide and the infection results in severe diseases, including Adult T-cell Leukemia (ATL) and HTLV-1 associated myelopathy (HAM). There are some limitations of employing the present commercial serological assays for both diagnostic and epidemiological purposes in different geographical areas of the Brazil, such as the Amazon Region. Currently, methods for diagnosis are usually expensive to adapt for routine use. The aim of this work was to identify and characterize specific ligands to IgG that mimic HTLV-1 epitopes through the Phage Display technique, which could be used for diagnosis and as future vaccine candidates. Initially, IgG from 10 patients with HTLV-1 and 20 negative controls were covalently coupled to protein G-magnetic beads. After biopanning, genetic sequencing, bioinformatics analysis and Phage-ELISA were performed. The technique allowed the identification of 4 clones with HTLV-1 mimetic peptides, three aligned with gp46, A6 (SPYW), B6 (SQLP) and D7 (PLIL), and one with the protease and Tax, A8 (SPPR). Clones A6 and B6 showed higher values of accessibility, antigenicity and hydrophilicity. The reactivity of the clones evaluated by the Receiver Operating Characteristic (ROC) curve showed that the B6 clone had the highest Area Under Curve (0.83) and sensitivity and specificity values (both were 77.27 %; p < 0.001). The study showed that the Phage Display technique is effective for the identification of HTLV-1-related peptides. Clone B6 indicated to be a good marker for bioprospecting diagnostic test for HTLV-1 infection and could be used as a possible vaccine candidate for future studies.